The Effect of Green Innovation, Green Investment, Environmental Performance, Financial Performance, and Company Age on Company Value - Fitriyati Arlyta DEWI; Titik ARYATI (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the effect of green innovation, green investment, environmental performance, financial performance, and company age on the value of companies listed on the Indonesia Stock Exchange during the period 2021-2023. The research sample consists of energy sector companies listed on the Indonesia Stock Exchange during the period and have published audited annual reports. Using the purposive sampling method, 29 companies were selected as samples, resulting in a total of 87 observation data. The data analysis method used in this study is panel data regression with data obtained from annual reports, audited financial reports and sustainability reports. The results of the study show that only financial performance has a positive effect. Meanwhile, green innovation, green investment, environmental performance and company age do not have a significant effect on company value. In addition, company size as a control variable does not affect company value.